1970
DOI: 10.1002/jso.2930020410
|View full text |Cite
|
Sign up to set email alerts
|

Delayed wound closures based on bacterial counts

Abstract: There exists a quantitative relationship between bacterial contamination and clinical infection. Because of this relationship, delayed wound closure can be performed based on the number of viable bacteria present in the incision a t the time of closure. This principle was applied to 95 delayed wound closures in a prospective series. Ninetythree cases were closed when the bacterial estimate was l o 5 bacteria or fewer per gram of tissue. This resulted in a 96% successful closure rate. The method of bacterial qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(62 citation statements)
references
References 10 publications
7
52
0
3
Order By: Relevance
“…In this study, quantification was determined by using superficial wound swab samples. Similar observations, placing emphasis on counts in tissue biopsy specimens, were reported in studies involving skin graft survival in experimental wounds inoculated with various types of bacteria (126), pressure ulcer healing (203), and delayed closure of surgical wounds (204,205). Aligned with this early work and in recognition of the fact that quantitative culture of tissue biopsy specimens was demanding on the microbiology laboratory (102) and was of minimal value in facilitating prompt wound management (202), a rapid Gram stain technique was shown to reliably predict a microbial load of Ͼ10…”
Section: Significance Of Microorganisms In Woundssupporting
confidence: 62%
“…In this study, quantification was determined by using superficial wound swab samples. Similar observations, placing emphasis on counts in tissue biopsy specimens, were reported in studies involving skin graft survival in experimental wounds inoculated with various types of bacteria (126), pressure ulcer healing (203), and delayed closure of surgical wounds (204,205). Aligned with this early work and in recognition of the fact that quantitative culture of tissue biopsy specimens was demanding on the microbiology laboratory (102) and was of minimal value in facilitating prompt wound management (202), a rapid Gram stain technique was shown to reliably predict a microbial load of Ͼ10…”
Section: Significance Of Microorganisms In Woundssupporting
confidence: 62%
“…[20][21][22] These studies included 50 skin graft patients with a mix of VLUs, traumatic, and burn wounds, 20 40 patients requiring delayed surgical closures (types of wounds not otherwise described), 22 and 95 surgical incisions requiring delayed surgical closure. 21 All of these studies demonstrated > 90% graft survival or successful delayed surgical closure only when bacterial colonization was £10 5 CFU/g and < 20% successful closure when bacterial colonization was > 10 5 CFU/g. Unfortunately, the results have not been as clear in studies of wounds healing by secondary intention without further surgical intervention.…”
Section: Microbial Loadmentioning
confidence: 99%
“…B. bei chronischen Dekubitalulzera und die Virulenz des Keims z. B. bei β-hämo-lysierenden Streptokokken von Bedeutung [19,34]. Semiquantitative Wundabstriche erwiesen sich als hilfreich, um die Ausprägung der Bakterienzahl einordnen zu können, obgleich es keinen spezifischen Grenzwert gibt [39].…”
Section: Diagnoseunclassified